Fruit Quality of New Early Ripening Strawberry Cultivars in Croatia - Sandra Voća; Nadica Dobričević; Verica Dragović-Uzelac; Boris Duralija; Jasmina Družić; Zlatko Čmelik; Martina Skendrović Babojelić (Food Technology and Biotechnology, 2008)
In this research fruit quality of seven early ripening strawberry cultivars (Clerry, Maya, Alba, Miss, Camarosa, Queen Elisa and Elsanta) during successive harvesting periods has been investigated. The following quality parameters were determined in the harvested fruits: dry matter, total soluble solids (TSS), pH, total acidity (TA), TSS/TA ratio, reducing sugars, sucrose, vitamin C, total anthocyanins, total phenolics (TP), nonflavonoids, flavonoids, antioxidant activity, and colour. Investigated cultivars differ significantly according to the basic chemical composition. The highest, statistically significant values of dry matter, soluble solids, TSS/TA ratio, vitamin C, total phenolics, nonflavonoids and antioxidant activity were determined for cultivar Elsanta. Among the other early ripening cultivars involved in the research, Alba and Maya had the lowest contents of dry matter, total soluble solids, total phenolics and nonflavonoids, reducing sugars and sucrose. The anthocyanin content was the highest in cultivars Camarosa, Miss and Maya; consequently, the most intensive colour was noted in the same cultivars. Parameters that determine fruit quality had lower values in all the investigated early ripening cultivars than in cultivar Elsanta; however, their quality was satisfactory.